EVALUACIÓN DEL SELLADO APICAL EN LA TÉCNICA CONDENSACIÓN LATERAL CON SELLADOR A BASE DE IONÓMERO DE VIDRIO. - Pineda Mejia, Martha Elena (1998)
In order to evaluate the effectiveness of the apical sealing abilities achieved with the glass ionomer cement Ketac Endo, it was prepared 40 single rooted teeth, using the biomechanical preparation technique "step back ", and then they were filled with Lateral Condensation technique. 20 of them used the Ketac Endo sealer and 20 the Grossman sealer After the process of ink apical leakage, the specimens were cleared up for the observation to Stereo microscope. The results indicated a smaller degree of apical microleakage for Ketac Endo sealer than Grossman sealer.